Mechanical Performances of Pressure Arch in Thick Bedrock during Shallow Coal Mining - Shuren Wang; Xiaogang Wu; Yanhai Zhao; Paul Hagan (Geofluids)
Due to the periodicity of mine pressure, it can easily lead to a wide-range damage of the overburden rock under shallow coal mining conditions, and the falling of the overburden rock is usually a serious threat to the mining safety. Based on the monitoring data of mine pressure in a typical shallow coal mine in northern China, the mechanical model of the surrounding rock in the mining field was built and the identification indicators of the pressure arch after coal mining was defined. Then, the arching mechanism, the stress distribution characteristics in different positions, and the bearing capacity of the pressure arch were analysed, and the evolution characteristics of the pressure arch under shallow horizontal coal mining were verified by numerical simulation and physical experiment. Results show that there is a core-bearing zone in the pressure arch, and the width of the core zone determines the bearing capacity of the pressure arch. The evolution of the pressure arch affects the formation and development of the caving arch of the loose zone in the mining field. The conclusions obtained in the study are of important theoretical value to direct the similar engineering practice.